APPLICATION OF BIODRYING TECHNOLOGY IN THE PROCESSING OF BRIQUETTES FROM ORGANIC WASTE IN LHOKSEUMAWE CITY - Nurkuzaifi, Muhammad; pardi, p; Putra, Alfian (Jurnal Sains dan Teknologi Reaksi, 2024)
ABSTRACT Waste is unwanted waste material after the end of a certain process. There are various processes that can be applied to produce dry waste using biodrying technology. The purpose of this study is to study biodrying technology for the processing of organic waste in Lhokseumawe City to become briquettes and the length of the biodrying process on the quality of briquettes produced from EM4 variations. This study used two independent variables, namely 14 and 21 days of biodrying process and EM4 variations, namely 100 ml, 200 ml, 300 ml, 400 ml and 500 ml. The results of this study show that those that meet the SNI No.1/6235/2000 standard are only ash content testing, volatility content and flame length test, while the moisture content test does not meet SNI No.1/6235/2000 standard.Keywords: Organic waste, biodrying and SNI No.1/6235/2000.